Fitting factor analysis of the Doreme I and II basic pattern system on size m blouses - Dia Ayu Candra, Fira; Eko Puji Rahayu , Sri; Kusumawardani , Hapsari (Meraki: Journal of Creative Industries, 2024)
The Doreme I and II pattern system is not quite popular. This research aimed to observe the fitting factor on women’s blouses using the Doreme I and II basic pattern system on a medium size blouse. This study used the descriptive method and quantitative approach. Instruments such as questionnaires containing 14 indicators of fitting factor were used to analyze the fit with percentage analysis. Based on the Doreme I pattern assessment on an M-size blouse, the fitting factor result was a poor fit. The results were 54.76% in the fit category, 28.57% in the poor fit category, and 16.678% in the not fit category. Meanwhile, the Doreme II pattern assessment on the M-size blouse obtained a fitting factor in the fit category. The results were 71.42% in the fit category, 19.04% in the poor fit category, and 11.9% in the not fit category. Also, according to the analysis, the Doreme II pattern had a precise position in several parts, while in Doreme I, due to the various additional numbers causing the dart to cross the bust circumference line. Thus, the bust circumference line must be adjusted to avoid a higher dart position.